Contributing Factors to Mobile Financial Fraud within Kenya - Owiti, Shadrack Ochieng; Ogara, Solomon; Rodrigues, Anthony (EPRA International Journalof Research and Development (IJRD), 2023)
The expansion of mobile banking services has created various challenges to financial sectors i.e. SIM swapping, hacking identity theft, social engineering, denial of service attack and account take over. The perceived criminal actions are due to continuous growth of mobile banking and computer networks. The identified challenges of rise in mobile financial fraud are due to lack of proper strategies to curb mobile fraud. This study investigated factors contributing to mobile financial fraud within Kenya. The study used both qualitative and quantitative method of data collection. The developed framework was informed by Fraud Triangle Theory (FTT). The findings confirmed that the fraud triangle is very helpful when applied to factors contributing to mobile financial fraud. Finally, the result of findings will have significant implications to financial institution policymakers, academic researchers, anti-fraud organizations and Central Bank of Kenya.
Keywords: Contributing Factors; Financial Fraud; Mobile; Within Kenya; Fraud Triangle; Factors; Determine